2010
DOI: 10.1590/s1807-59322010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Electric Countershock and Cold Stress Effects on Liver and Adrenal Gland

Abstract: OBJECTIVES:Cold exposure induces glycogen and lipid depletion in the liver and the adrenal gland, respectively. However, no previous study has determined the effects of electrical countershock on those tissues. We aimed to evaluate the effects of electrical countershock on lipid depletion in the adrenal gland and on glycogen depletion in the liver.METHODS:We used 40 male Wistar rats divided into four groups: the control group, in which the animals were subjected to a resting period of seven days; the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Concordance of measurements performed by the three investigators was evaluated and analyzed by * Bartko's intra-class correlation coefficient according to Fleiss guidelines [20], which was validated in previous studies [7,9,15,16] (p < 0.05, level of significance).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordance of measurements performed by the three investigators was evaluated and analyzed by * Bartko's intra-class correlation coefficient according to Fleiss guidelines [20], which was validated in previous studies [7,9,15,16] (p < 0.05, level of significance).…”
Section: Methodsmentioning
confidence: 99%
“…Induced cold state by low temperature exposure is considered as an important stressing physical agent [ 6 ]. Previous studies reported that acute exposure to cold stress besides impair heart tissue [ 7 - 9 ] cause lipid depletion in adrenal gland and glycogen depletion in liver [ 10 ], suggesting that the sympathetic activity and oxidative stress are the source of such fact.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant difference in the number of PCNA‐A and PCNA‐E between castrated and control animals could be established in the present study. However, histomorphological changes were observed, which are well‐known signs of a hyperstimulated adrenal cortex (Ferreira et al, 2010; Gannouni, Mhamdi, el May, Tebourbi, & Rhouma, 2014). In addition, the observed vacuolar degeneration of many ZF cells is a nonspecific lesion associated with stress states (Howard, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy may be defined as myocardial involvement without definitive etiology, characterized by left ventricle hypertrophy (rarely right ventricle), with myofibrillar disorder, increased left ventricular ejection fraction and decreased cardiac output, which depends on the functional impairment degree [ 41 - 47 ]. The outflow tract obstruction may exist or not.…”
Section: Discussionmentioning
confidence: 99%